Correlative Nanomechanical Measurements for Complex Engineered Systems. Issue 12 (2016) - Hintsala, Eric D.; Asif, Syed; Stauffer, Douglas D.
ABSTRACT: Multilayered film stacks, with length scales less than 10 nm are commonly used in a variety of devices, but present significant challenges to mechanical testing and evaluation. This is due to property convolution of the different layers. Both the properties of the individual layers and the combined response of the film stack are important input for design optimization. Here, we present ex-situ nanoindentation of a film stack representative of a perpendicular magnetic recording (PMR) hard disc drive (HDD), with more than 10 layers. We then compare this with in-situ transmission electron microscopy indentation to visualize deformation of individual layers of the stack. The ex-situ testing reveals early plastic deformation, with an initially high contact pressure (13 GPa) and modulus ( >160 GPa), followed by significant softening (8 GPa contact pressure and 140 GPa modulus), then slight hardening to 9 GPa. From in-situ testing, it is revealed that the metallic layer directly under the diamond like carbon (DLC) contributes the majority of the deformation and plastic flow, which is in turn constrained by a metallic oxide.